An Evolutionary Approach to Binge Drinking Impression Formation: A Cross-Cultural Comparison Between France and Peru - Boudesseul, Jordane (2020)
Evolutionary medicine proposes studying alcohol use and abuse through the lens of modern evolutionary theory. This study (https://osf.io/p48uw/) follows this approach and uses an evolutionary framework to predict how young adults (18–35 years old) form impression of a binge drinker. We predicted that displaying sexual dysfunctions (short-term risk) in a binge drinking video would negatively influence attitudes and expectations of a target when compared to cognitive (short-term risk) or long-term deficits. In the following studies, we use a Zahavian framework to understand and influence impression formation of a male binge drinker among women (intersexual selection) and men (intrasexual competition) participants in a subsequent task. Via a randomized experimental online study in France (N = 177, M = 23.39 [4.91], 43.50% men) and a preregistered conceptual replication study in Peru (N = 176, M = 25.61 [4.76], 53.41% men), women exposed to a binge drinking video—describing sexual impotence after a binge drinking episode—tended to downgrade attractiveness evaluation of the binge drinker. However, male participants were not impacted by the different types of signals displayed in the videos. These results show that evolutionary theory could help us understand impression formation in binge drinking context and call for gender-specific health messages.